2004
DOI: 10.1038/sj.bjp.0705757
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of canine bradykinin receptors in prostatic culture and in isolated prostate

Abstract: 1 The objective of this study was to characterize pharmacologically bradykinin (Arg-Pro-Pro-GlyPhe-Ser-Pro-Phe-Arg, BK) receptors in the canine prostate. 2 Primary cultures of canine prostate stromal (PS) and epithelial cells (PE) were established and then characterized using cell-specific antibodies (actin, vimentin and cytokeratin). Cultured cells were assayed for BK receptors using fluorometric imaging plate reader assays. In addition, isolated strips of the canine prostate were studied for BK-induced isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…We chose canine tissues as our study materials for the following reasons: (1) It would save us from sacriWcing new animals for our current study, (2) results from previous histological (Murray et al 2004), pathophysiological (KirchhoV 2002), pharmacological (Srinivasan et al 2004), and transplantation (Storb and Thomas 1985) experiments have demonstrated better correlation between canine and human subjects than mouse or other common experimental animals, and (3) our anti-PC-NЈ mAb and anti-PC-CЈ pAb recognize the extracellular species-variable and the cytoplasmic conserved domains of canine PC protein, respectively. Combinatory use of two antibodies thus enhances the accuracy in the interpretation of our results, which are summarized in Table 1, through cross-reference of the immunostaining patterns.…”
Section: Resultsmentioning
confidence: 99%
“…We chose canine tissues as our study materials for the following reasons: (1) It would save us from sacriWcing new animals for our current study, (2) results from previous histological (Murray et al 2004), pathophysiological (KirchhoV 2002), pharmacological (Srinivasan et al 2004), and transplantation (Storb and Thomas 1985) experiments have demonstrated better correlation between canine and human subjects than mouse or other common experimental animals, and (3) our anti-PC-NЈ mAb and anti-PC-CЈ pAb recognize the extracellular species-variable and the cytoplasmic conserved domains of canine PC protein, respectively. Combinatory use of two antibodies thus enhances the accuracy in the interpretation of our results, which are summarized in Table 1, through cross-reference of the immunostaining patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies suggest proliferation‐stimulating effects mediated by B1 and B2 receptors under physiological and pathophysiological conditions, such as in normal and tumor breast epithelial cells , endothelial cells , normal, and tumor cells from prostate , and fibroblasts . On the other hand, kinin receptors may act by inhibiting cell proliferation, such as for example, observed for breast stromal cells , kidney cells , and gingival fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
“…In dogs and in humans, adrenergic alpha 1A receptor subtype is the principal mediator of prostatic tone [31]. In addition, the dog prostate contracts by stimulating muscarinic [32], endothelin [33], and bradykinin receptors [26]. Thus, antagonism of endothelin, bradykinin, and neurokinin receptors represent novel therapeutic targets for relieving outlet obstruction in males as a result of prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal and epithelial cells were cultured from canine (4-6 years old) prostate tissue using the method of Srinivasan et al [26] with minor modification. Cells were characterized by morphological appearance and by the expression of cell specific markers; stromal cells were characterized by positive immunofluorescence staining for SMA, vimentin, desmin, and epithelial cells were characterized by positive staining for high molecular weight cytokeratin.…”
Section: Culture Of Canine Prostate Epithelial and Stromal Cellsmentioning
confidence: 99%